A library of functional recombinant cell-surface and secreted P. falciparum merozoite proteins. - Crosnier, C; Wanaguru, M; McDade, B; Osier, F; Marsh, K; Rayner, J; Wright, G (2013)
Malaria, an infectious disease caused by parasites of the Plasmodium genus, is one of the world's major public health concerns causing up to a million deaths annually, mostly because of P. falciparum infections. All of the clinical symptoms are associated with the blood stage of the disease, an obligate part of the parasite life cycle, when a form of the parasite called the merozoite recognizes and invades host erythrocytes. During erythrocyte invasion, merozoites are directly exposed to the host humoral immune system making the blood stage of the parasite a conceptually attractive therapeutic target. Progress in the functional and molecular characterization of P. falciparum merozoite proteins, however, has been hampered by the technical challenges associated with expressing these proteins in a biochemically active recombinant form. This challenge is particularly acute for extracellular proteins, which are the likely targets of host antibody responses, because they contain structurally critical post-translational modifications that are not added by some recombinant expression systems. Here, we report the development of a method that uses a mammalian expression system to compile a protein resource containing the entire ectodomains of 42 P. falciparum merozoite secreted and cell surface proteins, many of which have not previously been characterized. Importantly, we are able to recapitulate known biochemical activities by showing that recombinant MSP1-MSP7 and P12-P41 directly interact, and that both recombinant EBA175 and EBA140 can bind human erythrocytes in a sialic acid-dependent manner. Finally, we use sera from malaria-exposed immune adults to profile the relative immunoreactivity of the proteins and show that the majority of the antigens contain conformational (heat-labile) epitopes. We envisage that this resource of recombinant proteins will make a valuable contribution toward a molecular understanding of the blood stage of P. falciparum infections and facilitate the comparative screening of antigens as blood-stage vaccine candidates.